High capacity monoclinic Nb₂O₅ and semiconducting NbO₂ composite as high-power anode material for Li-Ion batteries - Park, Hyunjung (2021)
Niobium pentoxide, Nb2O5, is an intercalation-type material with a high theoretical capacity of ∼404 mAh g−1 for Li-ion batteries. However, electrochemical properties of Nb2O5 largely depend on its various polymorphs with different crystal structures, and their low electrical conductivity acts as the main obstacle. Here, we report high-temperature calcined monoclinic Nb2O5 and semiconducting NbO2 composite as a high-power anode material. Monoclinic Nb2O5 itself as a main active material shows a high capacity of ∼280 mAh g−1, and NbO2 with a small band gap of ∼0.5 eV not only improves electrical conductivity but also gives a capacity of ∼110 mAh g−1. To have a synergic effect of these two materials, the Nb2O5/NbO2 composite is prepared via simple post-calcination of as-prepared Nb2O5 under a reduction atmosphere. It shows a discharge capacity of ∼214 mAh g−1 at 0.05 C, a high initial Coulombic efficiency of 94.7%, a superior rate capability of ∼40 mAh g−1 at 100 C, and a robust cycle performance of 81% retention over 900 cycles.